Leilões 3G europeus e brasileiros: uma sugestão a fertilização - Valente, Paulo Vicente Dutra da Silva Santos (2006)
A research was accomplished on the UMTS frequency spectrum licensing on Europe on the years 2000 and 2001. It was analyzed the bidders behaviors’, the auction rules’, the auction environment and each auction objective. After the European auction analysis was done a discussion on the specifics aspects of brazilian market for those types of auction.